Coagulation in Brain Tumors: Biological Basis and Clinical Implications - Mandoj, Chiara; Tomao, Luigi; Conti, Laura (Frontiers in Neurology, 2019)
Cancer patients commonly show abnormal laboratory coagulation tests, indicating a subclinical hypercoagulable condition that contribute to morbidity and mortality. The hypercoagulation status not only increases the risk of thromboembolic events but also influences the tumor biology promoting its growth and progression by stimulating intracellular signaling pathways. Recent molecular studies characterized the role of oncogene and repressor gene in activating clotting pathways, as an integral feature of the neoplastic transformation. It is now clear how haemostatic processes, activated by cancer cells harboring oncogenic mutations, rely on the molecular profile of a particular malignancy, an aspect particularly evident in the differential coagulome profiles showed by different molecular subtypes of brain tumors, such as glioblastoma and medulloblastoma. This review focuses on the biological and clinical aspects of haemostasis in cancer with particular regard on brain tumors.